Diagnostic challenges in the diagnosis and treatment of ovarian cancer in Lynch syndrome - Protasiuk, Agnieszka; Żak, Agata; Sierzpowski, Rafał; Tymoszuk, Patrycja; Kasperek, Bartosz; Augustowska, Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction and purpose Lynch syndrome (LS), also known as hereditary nonpolyposis colorectal cancer (HNPCC), is an autosomal dominant genetic disorder characterized by a significantly increased risk of developing various malignancies, including ovarian cancer. This study aims to analyse the risk of ovarian cancer development in patients with Lynch syndrome and to compare the diagnostic and therapeutic approaches for this neoplasm in the context of sporadic cases. Description This discussion explores the genetic mechanisms underlying mutations in mismatch repair (MMR) genes, such as MLH1, MSH2, MSH6, and PMS2, which are essential for maintaining genomic stability. The diagnostic criteria, including the Amsterdam Criteria and the Bethesda Guidelines, are reviewed. The paper highlights the diagnostic challenges posed by the nonspecific symptoms of ovarian cancer and emphasizes the importance of early detection and monitoring. A comprehensive review of treatment modalities is also provided, covering surgical cytoreduction, chemotherapy, and emerging therapies, such as immunotherapy and cancer vaccines. The importance of interdisciplinary care for patients is underscored, along with the need for preventive measures and health education to manage cancer risk. Summary Despite the challenges associated with diagnosis and treatment, the prognosis for patients with ovarian cancer linked to Lynch syndrome is generally more favourable than for those with sporadic cancers. This can be attributed to earlier diagnosis and the favourable histopathological characteristics of tumours associated with Lynch syndrome.